Improving a PCR-based method for identification of Ralstonia solanacearum in natural sources of West Malaysia - Khakvar, Reza; Sijam, Kamaruzaman; Wong, Mui Yun; Radu, Son; Thong, Kwai Lin (Science Publications, 2008)
Ralstonia solanacearum, a soil-borne plant pathogen, causes lethal wilting disease of more than 200 plants worldwide. This very wide host range covers both monocots and dicots, extending from annual plants to trees and shrubs. Although generally it’s considered as a plant pathogen, R. solanacearum behaves primarily as a saprophytic bacterium able to survive for long periods of time in various natural habits such as surface waters and different types of soils. Epidemiological and ecological studies on pathogen distribution in the environment are seriously hindered by the lack of efficient detection method especially when the concentration of the pathogen is either very low or is present in a latent, dormant or non-culturable state. With due attention to importance of R. solanacearum in Malaysia and several irreparable losses that every year caused by this bacterium, this is promted current study to develop a sensitive PCR-Based method to improve the detection of R. solanacearum in natural sources. We selected the previously reported primers (OLI1; OLI2; Y2; JE2) for their sensitivity and specificity detection of the bacterium in water and soil by a modification of PCR assay.